THE INFLUENCE OF SCHOOL PRINCIPALS' TRANSFORMATIONAL LEADERSHIP AND TEACHERS' COMMITMENT ON PRIMARY SCHOOL TEACHERS' PROFESSIONAL COMPETENCIES - MERIYANTI, Fetty (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2023)
The purpose of this study is to investigate: The influence of the principal's transformational leadership on the commitment of teachers of Public Elementary Schools in Prohibition District, Tangerang City. The research approach used in this study is a quantitative approach. The population in this study was all teachers of State Elementary Schools in Prohibition District, Tangerang City with a sample of 211 teachers taken randomly (random sampling). The analysis technique used is the path analysis technique. Based on the analysis, it is known: 1) There is a direct positive and significant influence of Transformational Leadership of Principals on the Professional Competence of Public Elementary School Teachers in Prohibition Distric, Tangerang City. This is evident from the results of the calculated t value > t table (4,373 > 1,652) and the path coefficient value of 0.285. 2) There is a direct positive and significant influence Teacher commitment to the Professional Competence of State Elementary School Teachers in Prohibition District, Tangerang City. This is evident from the results of the calculated t value of the table t > (3,629 > 1,652) and the path coefficient value of 0.237. 3) There is a direct positive, and significant influence of the Principal's Transformational Leadership on the Commitment of Public Elementary School Teachers in Prohibition District, Tangerang City. This is evident from the results of the calculated t value > ttable (3,783 > 1,652) and the path coefficient value of 0.253.